Prior high corticosterone exposure reduces activation of immature neurons in the ventral hippocampus in response to spatial and nonspatial memory. Issue 3 (29th November 2014) - Workman, Joanna L.; Chan, Melissa Y.T.; Galea, Liisa A.M.
ABSTRACT Chronic stress or chronically high glucocorticoids attenuate adult hippocampal neurogenesis by reducing cell proliferation, survival, and differentiation in male rodents. Neurons are still produced in the dentate gyrus during chronically high glucocorticoids, but it is not known whether these new neurons are appropriately activated in response to spatial memory. Thus, the goal of this study was to determine whether immature granule neurons generated during chronically high glucocorticoids (resulting in a depressive‐like phenotype) are differentially activated by spatial memory retrieval. Male Sprague Dawley rats received either 40 mg/kg corticosterone (CORT) or vehicle for 18 days prior to behavioral testing. Rats were tested in the forced swim test (FST) and then tested in a spatial (hippocampus‐dependent) or cued (hippocampus‐independent) Morris Water Maze. Tissue was then processed for doublecortin (DCX) to identify immature neurons and zif268, an immediate early gene product. As expected, CORT increased depressive‐like behavior (greater immobility in the FST) however, prior CORT modestly enhanced spatial learning and memory compared with oil. Prior CORT reduced the number of DCX‐expressing cells and proportion of DCX‐expressing cells colabeled for zif268, but only in the ventral hippocampus. Prior CORT shifted the proportion of cells in the ventral hippocampus away from postmitotic cells and toward immature, proliferative cells, likely due to the fact that postmitotic cells were produced and matured during CORT exposure but proliferative cells were produced after high CORT exposure ceased. Compared with cue training, spatial training slightly increased DCX‐expressing cells and shifted cells toward the postmitotic stage in the ventral hippocampus. These data suggest that the effects of CORT and spatial training on immature neurons are more pronounced in the ventral hippocampus. Further, high CORT reduced activation of immature neurons, suggesting that exposure to high CORT may have long‐term effects on cell integration or function. © 2014 Wiley Periodicals, Inc.